Zinc(II) phthalocyanine containing Schiff base containing sulfonamide: synthesis, characterization, photophysical, and photochemical properties - Sahal, Hakan; Piskin, Mehmet; Organ, G. Atiye; Ozturk, O. Faruk; Kaya, Mehmet; Canpolat, Erdal (Taylor & Francis Ltd, 2018)
Synthesis and characterization of (E)-4-((5-bromo-2-(lambda(1)-oxidanyl)benzylidene)amino)-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamide (1), its substituted phthalonitrile derivative (2), and its tetra substituted zinc(II) phthalocyanine complex (3) were performed. Compounds 1, 2, and 3 were characterized by methods such as elemental analyses, FT-IR, H-1-NMR, C-13-NMR (except for 3), and MALDI-TOF mass spectra. The photophysical and photochemical properties of this substituted zinc(II) phthalocyanine complex aimed to be used as a photosensitizer were investigated in DMSO solution for determination of their photosensitizing abilities in photocatalytic applications such as photodynamic therapy (PDT). The influence of the substituent as a bioactive compound on the phthalocyanine skeleton on spectroscopic, photophysical, and photochemical properties were also determined and compared with unsubstituted zinc(II) phthalocyanine and some zinc(II) phthalocyanines containing different substituents previously studied. According to photophysical and photochemical investigations, 3 has potential as a photosensitizer for PDT. [GRAPHICS] .
Keywords: Sulfa drug; Schiff base; benzenesulfonamide; zinc(II) phthalocyanine; photosensitizer